Technology and Hybrid Multimedia for Language Learning and Cross-Cultural Communication in Higher Education - Farida, F.; Supardi, S.; Abduh, Amirullah; Muchtar, Jumardin; Rosmaladewi, R.; Arham, Muhammad (ASEAN Journal of Science and Engineering, 2024)
Technology and Hybrid Multimedia for Language Learning and Cross-Cultural Communication in Higher Education is a critical component of English language learning. The purpose of this study is to explore technology and hybrid multimedia for language Learning in English language learners (EFL) in higher education. This study aims to explore how cross-cultural communication skills affect learners' technology and hybrid multimedia learning experience and their English proficiency in the context of public university learning. In addition to that, this research uses a case study approach focusing on a group of EFL learners. The data is gathered via comprehensive interviews with EFL (English as a Foreign Language) learners to investigate their encounters and perspectives concerning cross-cultural communication. The interviews and observations are examined to identify and analyze the recurring themes. The results of the study revealed that English learners who have good cross-collaborative communication skills tend to have higher English proficiency. The study reveals that cross-communicative communication has a positive influence on English language proficiency, as it allows EFL learners to gain a deep understanding of various languages and cultures, enhancing their ability to interact with people from diverse cultural contexts effectively.